A Scale Development Study Intended for Mathematics Teacher Candidates: Mathematical Visualization Perception Scale - Ilhan, Aziz; Tutak, Tayfun (Modestum Ltd, 2021)
The aim of this study is to develop a valid and reliable measurement tool that measures mathematical visualization perceptions for mathematics teacher candidates. Therefore, the type of study is a survey research. Research was carried out with 462 (336 Female, 125 Male) mathematics teacher candidates from a university located in the Eastern Anatolia region Turkey in 2018-2019 spring season. Exploratory and confirmatory factor analyzes were performed for the analysis of research data. In the process of development of Mathematical Visualization Perception Scale (MVPS); the preparation of the pool of material, testing of the validity of the scope and appearance, conducting the trial application, ensuring the construction validity, calculating the reliability and establishing the final scale were followed. As a result of the exploratory factor analysis, a valid and reliable 5-point Likert-type scale consisting of 42 items, with 6 factors [Additional Drawing (AD), Spatial Thinking (ST), Direction Concept (DC), Relation with Daily Life (RDL), Transition from Algebra to Geometry (TAG) and Transition from Geometry to Algebra (TGA)] was created. Cronbach Alpha internal stability coefficient of these factors was calculated as 0.938. The factor structure of the scale was also confirmed by confirmatory factor analysis. As a result of the findings obtained, it was suggested to the researchers who will study in the related field to evaluate mathematical visualization perceptions of mathematics teacher candidates by using related scale with different sample groups or different variables.
Keywords: visualization perception; mathematical visualization; scale development; mathematics teacher candidates; mathematics education